2 а) (а-3)(а+3)
б) 2*х^2 + 1 - 4*х
в) 9*а^2 + 4 + 12*а
3) а) а^2 + 25 + 10*а + а^2 - 16 = 2*а^2 + 10*а + 9
= 2*(-1/2)^2 + 10*(-1/2) + 9 = 1/2 - 5 + 9 = 1/2 + 4 = 4.5
б) (6*а+6)*(6*а-6-6*а) = -6*(6*а+6) = -6*(3.5*6 + 6)= -165.6
в) 7*х^2 + 14*х -(х^2 + 49 + 14*х) = 7*х^2 + 14*х - х^2 - 49 - 14*х = 6*х^2 - 49 = 6*5^2 - 49 = 6 * 25 - 49 = 150 - 49 = 101
2 а) (а-3)(а+3)
б) 2*х^2 + 1 - 4*х
в) 9*а^2 + 4 + 12*а
3) а) а^2 + 25 + 10*а + а^2 - 16 = 2*а^2 + 10*а + 9
= 2*(-1/2)^2 + 10*(-1/2) + 9 = 1/2 - 5 + 9 = 1/2 + 4 = 4.5
б) (6*а+6)*(6*а-6-6*а) = -6*(6*а+6) = -6*(3.5*6 + 6)= -165.6
в) 7*х^2 + 14*х -(х^2 + 49 + 14*х) = 7*х^2 + 14*х - х^2 - 49 - 14*х = 6*х^2 - 49 = 6*5^2 - 49 = 6 * 25 - 49 = 150 - 49 = 101